Nanoparticles loaded with hepatic growth factor and insulin-like growth factor-1 improve left ventricular repair in a porcine model of myocardial Ischemia reperfusion injury. (25th November 2020) - Wu, M; Claus, P; De Buck, S; Veltman, D; Gillijns, H; Holemans, P; Pokreisz, P; Caluwe, E; Colino, E; Cohen, S; Prosper, F; Pelacho, B; et al.
Abstract: Introduction: Nanomedicine offers great potential for treatment of cardiovascular disease. We tested whether intramyocardial (IM) injection of pro-angiogenic hepatocyte growth factor (HGF) and anti-apoptotic, pro-myogenic insulin-like growth factor 1 (IGF-1) encapsulated in Alginate-Sulfate nanoparticles (AlgS-NP) improves left ventricular (LV) functional recovery in a porcine ischemia-reperfusion (I/R) model. Methods: Myocardial infarction (MI) was induced by 75min balloon occlusion of the mid-LAD followed by reperfusion. After 1w, pigs (n=12) with marked LV dysfunction (EF<45%) were randomized to fusion imaging-guided IM injections of 8 mg Cy5-labelled AlgS-NP loaded with 200μg HGF and IGF-1 (GF) or with phosphate-buffered saline (CON) using the MYOSTAR injection catheter. AlgS-NP retention in the heart was determined by measuring Cy5 levels in peripheral blood. At 8w, treatment effect was evaluated using cardiac magnetic resonance imaging and coronary flow reserve (CFR) measurements, and further assessed using sirius red staining to measure myocardial fibrosis. Results: At 1w after MI, LV ejection frqction (LVEF) was 37±5% (range 27–45%) and infarct size (IS)/LV mass 24±6% (range 19–38%). Myocardial retention of AlgS-NP was comparable between 2 groups (maximal systemic leakage after IM injection: 9% CON vs 20% GF, P=0.25). After 8 w, IS/LV mass decreased by one third in GF-treated pigs compared with 14% in CON (P=0.03, Fig. A) and was associated with a trend towards improvement in CFR (P=0.05, Fig. B). LVEF significantly increased in GF-treated pigs (6±2% vs. −1±1%, P=0.02, Fig. C), which was attributable to a greater reduction in end-systolic volume. The improvement in LVEF was also consistent with significant reduction of fibrosis (P=0.01, Fig. D) in the peri-infarct zone (PI). Conclusions: Intramyocardial injection of AlgS-nanoparticle-encapsulated HGF and IGF-1 to the ischemic myocardium significantly improves LV repair, and offers the prospect of innovative treatment for patients with refractory ischemic heart disease. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): EuroNanoMed, Horizon 2020